The Need Analysis for an Android-Based Marketplace Training Model to Improve Entrepreneurs' Product Marketing Capabilities in Barrokah Garbage Bank, Tulungrejo Village, Trucuk District - Nuraeni, Yeni; Sudiyanto, Sudiyanto; Setiawan, Abdul Haris (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Technology literacy is needed in this digital era. One of the important online marketing applications for entrepreneurs to market their product online is E-commerce but entrepreneurs in Tulungrejo Village, Trucuk are unskilled to use it. The purpose of this study was to obtain information about: (1) the training model used so far (previously) and product marketing capabilities; (2) a training model that can improve product marketing capabilities; and (3) the training model needed to improve the ability to market products for Barrokah Garbage Bank business actors in Tulungrejo Village, Trucuk District, Bojonegoro Regency. The type of research used is qualitative research methods. Information collection techniques in the form of data collection, data display, data reduction and conclusions. Analysis of measuring data through pre-test and post-test learning outcomes. The research subjects were 20 Barrokah Garbage Bank business actors in Tulungrejo Village, Trucuk District, Bojonegoro Regency. From the results of the study it was concluded: 1) the training model used previously did not exist, 2) the marketplace model can improve product marketing capabilities, and 3) the marketplace training model is needed to improve product marketing capabilities for Barrokah Garbage Bank business actors, Tulungrejo Village, Trucuk District, Bojonegoro Regency.